MAKING A DIGITAL LITERATION CULTURE IN A SOCIOLOGICAL PERSPECTIV : THE ROLE OF PARENTS IN DEVELOPING EARLY CHILDHOOD DIGITAL LITERACY - BAKHTIYAR (CV KULTURA DIGITAL MEDIA, 2021)
The study aims to describe the role of parents in realizing a digital literacy culture for early childhood. The object of research is in-depth, based on analyzing detailed comprehensive studies of various content, the role of parents in assisting children's digital literacy. The research has the scope of basic analysis based on the study of the role of the family in education, the role of parents in learning assistance and digital literacy in order to realize a digital literacy culture for early childhood. The analysis requires realistic critical thinking, for the sake of applying concepts to historical periods, both past and present, so that it is appropriate to apply the historical approach, characterized by the dominance of realistic critical investigation of the development of thought or terms, while primary information sources are used as primary data. Collecting data to make optimal use of the research library, reading various literature. Analyzing research, fully using descriptive qualitative analysis, based on various sources of analysis of theoretical reading, research and non-research. Research occurs in the dominance of descriptions of factual facts, to obtain solutions to various problems in social phenomena. Research validation requires the application of content analysis, to analyze the meaning of various concepts in the research being carried out. Observation of the role of parents for learning assistance and digital literacy of children, empowered every day as the most important element to support theory construction. The results showed that the involvement of parents in realizing children's digital literacy culture is very important for the development of children's potential. The process of digital literacy education from an early age is very positive and constructive, it must be carried out continuously and in a structured manner, starting from the family environment, educational institutions, society and government, providing facilities, expanding access to information sources and learning resources, increasing public participation, strengthening governance and managing people's roles old.